Safety, mid-term outcomes and quality of life after eTEP repair for ventral hernia: A prospective study of 100 consecutive patients - La, Van Phu; Doan, Anh-Vu; La, Vinh-Phuc (Acta Biomedica Atenei Parmensis, 2026)
Background: The extended-view totally extraperitoneal (eTEP) technique is a minimally invasive approach for ventral hernia repair that allows retromuscular mesh placement without entering the peritoneal cavity. However, prospective data on its safety and mid-term outcomes remain limited. This study aimed to evaluate the safety and mid-term outcomes of eTEP repair.Methods: This prospective study included 100 consecutive patients undergoing eTEP repair. Demographic, clinical, operative, and follow-up data were analyzed. Quality of life was assessed using the EuraHS-QoL questionnaire, with changes over time evaluated by the Friedman test and Wilcoxon signed-rank test.Results: The mean patient age was 57.4 ± 12.9 years (range 31–88) and 65% were female. Primary hernias accounted for 54% of cases and incisional hernias for 46%. Standard eTEP repair was performed in 88% of patients, while 12% required transversus abdominis release (TAR). The mean operative time was 132 ± 47 minutes and hybrid conversion occurred in 9% of cases. The median hospital stay was 4 days (range 2–8). Early complications included seroma (7%), surgical-site infection (2%), hematoma (2%), ileus (1%), cellulitis (1%), and paresthesia (1%). Two bowel injuries (2%) occurred, including one intraoperative enterotomy and one unrecognized injury requiring reoperation. After a median follow-up of 21.9 months (range 6–39), hernia recurrence occurred in two patients (2%). Chronic postoperative pain occurred in 4% of patients and was mild. Late mesh infection occurred in two patients (2%). Quality of life improved significantly over time (Friedman test, p < 0.001), with significant improvements observed at all postoperative time points compared with preoperative values (all p < 0.001).Conclusions: eTEP repair is a safe and feasible minimally invasive technique for ventral hernia repair, associated with low complication and recurrence rates and significant improvement in patient-reported quality of life.